2015
DOI: 10.1039/c4ob01770f
|View full text |Cite
|
Sign up to set email alerts
|

Cationic dialkylarylphosphates: a new family of bio-inspired cationic lipids for gene delivery

Abstract: In this work that aims to synthesize and evaluate new cationic lipids as vectors for gene delivery, we report the synthesis of a series of cationic lipids in which a phosphate functional group acts as a linker to assemble on a molecular scale, two lipid chains and one cationic polar head. The mono or dicationic moiety is connected to the phosphate group by an aryl spacer. In this work, two synthesis strategies were evaluated. The first used the Atherton-Todd coupling reaction to introduce a phenolic derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Some transfection reagents are currently used to introduce miRNAs into cells, but poor transfection efficiency and low expression level of miRNAs are a common problem in neurons. The cationic lipofection has been shown to perform well in many passage cells, such as osteoclasts , endothelial cells (Rohde et al, 2015), and human-derived epithelial cells (Le Corre et al, 2015), but the mature primary cells, like neurons, are still described as difficult-totransfect (Morris and Labhasetwar, 2015). In some studies, the cationic lipofection reagents, like Lipofectamine 2000, were efficient in terms of delivery in primary cells (Chen et al, 2014), but there are no special protocols to maintain the functionality of the internalized RNA oligos.…”
Section: Discussionmentioning
confidence: 99%
“…Some transfection reagents are currently used to introduce miRNAs into cells, but poor transfection efficiency and low expression level of miRNAs are a common problem in neurons. The cationic lipofection has been shown to perform well in many passage cells, such as osteoclasts , endothelial cells (Rohde et al, 2015), and human-derived epithelial cells (Le Corre et al, 2015), but the mature primary cells, like neurons, are still described as difficult-totransfect (Morris and Labhasetwar, 2015). In some studies, the cationic lipofection reagents, like Lipofectamine 2000, were efficient in terms of delivery in primary cells (Chen et al, 2014), but there are no special protocols to maintain the functionality of the internalized RNA oligos.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary data (experimental procedures, characterization data, 1 H, 31 P, 13 C spectra for all compounds and mass spectrometry analysis) associated with this article can be found, in the online version, at http://dx.doi.org/10.1016/j.tetlet.2015.03.093.…”
Section: Supplementary Datamentioning
confidence: 99%
“…To improve the efficacies of cationic amphiphiles for nucleic acids delivery, both the modification of the structure of the polar head group (e.g. nature of the cationic charge [22] polycationic moieties [23,24] ) and the structure of the hydrophobic domain were explored. [25] In the last case, it was shown that cationic amphiphiles containing saturated lipid chains produced ineffective pDNA carriers.…”
Section: Introductionmentioning
confidence: 99%